Is Less Really More? Economic Evaluation of Minimally Invasive Surgery. Issue 1 (April 2021) - Chung, Andrew S.; Ballatori, Alexander; Ortega, Brandon; Min, Elliot; Formanek, Blake; Liu, John; Hsieh, Patrick; Hah, Raymond; Wang, Jeffrey C.; Buser, Zorica
Study Design: Review. Objective: A comparative overview of cost-effectiveness between minimally invasive versus and equivalent open spinal surgeries. Methods: A literature search using PubMed was performed to identify articles of interest. To maximize the capture of studies in our initial search, we combined variants of the terms "cost, " "minimally invasive, " "spine, " "spinal fusion, " "decompression" as either keywords or MeSH terms. PearlDiver database was queried for open and minimally invasive surgery (MIS; endoscopic or percutaneous) reimbursements between Q3 2015 and Q2 2018. Results: In general, MIS techniques appeared to decrease blood loss, shorten hospital lengths of stay, mitigate complications, decrease perioperative pain, and enable quicker return to daily activities when compared to equivalent open surgical techniques. With regard to cost, primarily as a result of these latter benefits, MIS was associated with lower costs of care when compared to equivalent open techniques. However, cost reporting was sparse, and relevant methodology was inconsistent throughout the spine literature. Within the PearlDiver data sets, MIS approaches had lower reimbursements than open approaches for both lumbar posterior fusion and discectomy. Conclusions: Current data suggests that overall cost-savings may be incurred with use of MIS techniques. However, data reporting on costs lacks in uniformity, making it difficult to formulate any firm conclusions regarding any incremental improvements in cost-effectiveness that may be incurred when utilizing MIS techniques when compared to equivalent open techniques.